Pengaruh Penerapan ESG Terhadap Nilai Perusahaan di Indonesia - Jeanice Jeanice; Sung Suk Kim (Politeknik Ganesha Medan, 2023)
The development of the application of environmental, social, and governance aspects for companies continues to increase. This can be seen by the growing sustainability investment from many companies that pay attention to good environmental, social, and governance aspects. Companies in Indonesia that are listed on Indonesian stock exchange and implement environmental, social, and governance continue to experience an increase in massive exploitation of resources for large financial gains causing enormous environmental damage. This study aims to investigate the effect of environmental, social, and governance on firm value in Indonesia. Firm value will be measured using return on equity and price book value. Meanwhile, environmental, social, and governance will be measured using the environmental, social, and governance index value. A total of 45 companies on the Indonesian Stock Exchange for 3 years from 2018-2020 were used. The effect of environmental, social, and governance on company performance is measured using a panel model after correcting violations of its assumptions. The results showed that the environmental, social, and governance variable had a negative and significant effect on return on equity and had no effect on simplified Tobin's. Companies need to improve environmental, social, and governance performance due to the low environmental, social, and governance values during this research period. Improved environmental, social, and governance performance is expected to improve other aspects including company performance